2013
DOI: 10.1016/j.jhydrol.2013.01.045
|View full text |Cite
|
Sign up to set email alerts
|

A novel architecture for pore network modelling with applications to permeability of porous media

Abstract: Network models of porous media are beneficial for predicting the evolution of macroscopic mass transport properties. This work proposes a novel bi-regular network model based on truncated octahedral support. With the model, pore systems with different pore coordination spectra for a given average coordination number can be constructed to match experimental data. This feature and the maximum allowed pore coordination of 14 make the proposed model more realistic and flexible than the existing models based on cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…One remedy is to construct a network based on a regular cellular complex which represents the spatial distribution of pores in an average sense, i.e., to perform a prior "geometric homogenisation" of the medium. In a previous work (Jivkov et al 2013) we have proposed a complex of compactly packed truncated octahedral cells, Fig. 2a, considering that a cell of this shape represents the average neighbourhood of a pore in a material.…”
Section: Previous Modelling and Present Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…One remedy is to construct a network based on a regular cellular complex which represents the spatial distribution of pores in an average sense, i.e., to perform a prior "geometric homogenisation" of the medium. In a previous work (Jivkov et al 2013) we have proposed a complex of compactly packed truncated octahedral cells, Fig. 2a, considering that a cell of this shape represents the average neighbourhood of a pore in a material.…”
Section: Previous Modelling and Present Approachmentioning
confidence: 99%
“…This is a mapping, suitable for pore systems containing predominantly spherical pores with connectivity and throat size statistics obtained from experimental data (Jivkov et al 2013). It is also suitable for pore systems with only pore size distribution available from experimental techniques.…”
Section: Previous Modelling and Present Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonate rocks usually present a wide range of permeability for the same porosity value because of a marked variability in the connectivity of pores, both with respect to average coordination number (the number of neighboring pores) and pore-throat diameter (Lucia, 2007;Ahr, 2008;Hollis et al, 2010;Jivkov et al, 2013). Raoof and Hassanizadeh (2012) showed the importance of including the coordination number to estimate the permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Raoof and Hassanizadeh (2012) showed the importance of including the coordination number to estimate the permeability. Later, Jivkov et al (2013) demonstrated that the coordination number is a more important control parameter on permeability than total porosity. However, the pore geometry, pore-throat radius, and coordination number cannot be reliably quantified using thin-section images, because three-dimensional (3-D) information cannot be assessed.…”
Section: Introductionmentioning
confidence: 99%